Effect of natural latex membranes on wound repair of palate donor areas: A pilot randomized controlled trial study, including the membranes characterization - Spin, José Rodolfo [UNESP]; de Oliveira, Guilherme José Pimentel Lopes; Spin-Neto, Rubens; Herculano, Rondinelli Donizetti [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP] (Elsevier, 2021)
The aim of the present study was to evaluate the use of an exclusively developed latex membrane, to act as physical barrier to aid wound healing, epithelization, and pain in the palate region after free gingival graft harvesting. Latex membranes were physically, chemically, and mechanically characterized before application. Twenty-four patients (age 30–70 years, mean 45 years), requiring free gingival graft were sequentially selected, and randomly divided in two groups according to type of protection utilized on the donor site, control group (14 patients)- The wound in palate was covered with acrylic plate and surgical cement only and test group (10 patients) - The wound in palate was covered with the experimental latex membrane. The palate region was evaluated on the surgery day and 3, 7, 15, and 30 days after the surgical procedure for wound healing area, epithelization, bleeding, and self-reported pain (VAS). Wound reduction between periods was calculated, as percentage. The membrane had smooth surface, high elasticity, and nanoscale porosity, as expected for biomedical application. At 15 days, control group patients presented a fully healed wound, while mean wound closure was 98.6 % in the latex group. At 30 days, both groups presented complete wound closure. Also, at 30 days, there was no significant epithelization difference between the groups, and all patients in both presented fully epithelized wounds. As for bleeding, at 7 days it was positive for 21.4 % of the patients in the control group, while it was already negative for all patients in the latex group. Regarding reported pain, VAS values were larger in the control group, although with no statistical significance. Latex membranes did not delay the healing of the palate or caused visible adverse effects (i.e. allergies, discomfort, or injury to the patient), when compared to the control group.
Keywords: Latex membrane; Palate donor; Wound repair